Studies of Nondefective Adenovirus 2-Simian Virus 40 Hybrid Viruses IV. Characterization of the Simian Virus 40 Ribonucleic Acid Species Induced by Wild-Type Simian Virus 40 and by the Nondefective Hybrid Virus, Ad2(+)ND(1) - Oxman, Michael N. (1971)
Ad2(+)ND(1), a nondefective adenovirus 2 (Ad2)-simian virus 40 (SV40) hybrid virus, has been previously shown to contain a small segment of the SV40 genome covalently linked to Ad2 deoxyribonucleic acid (DNA). The SV40 portion of this hybrid virus has been characterized by relating the SV40-specific ribonucleic acid (RNA) sequences transcribed from the Ad2(+)ND(1) DNA to those transcribed from the DNA of SV40 itself. RNA-DNA hybridization-competition studies indicate that the SV40 component of Ad2(+)ND(1) consists of some, but not all, of that part of the SV40 genome which is transcribed early, i.e., prior to viral DNA replication, in SV40 lytic infection.